FINANCIAL MODELLING AS A TOOL FOR SOLVING THE MAIN PROBLEMS OF THE ENTERPRISE - MAZUR, Dmytro; MAZUR, Alexander; MAZUR, Galina; COWBY, Antonina (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article describes the development of theoretical provisions and the improvement of methodological approaches to the analysis and forecasting of the financial state of the company with the disclosure of the main problems that are solved with the help of financial modelling. The article analyzes the use of financial modelling and forecasting tools, which makes it possible to effectively analyze complex and uncertain situations related to strategic decision-making, is a tool for financiers that allows considering a large number of options according to the scenario of how to live without losing invested funds. The relevance of financial modelling is revealed when the availability and cost of external financing decreases, the risks of loss of liquidity and business stability increase, and the most important condition for its development is the increase in operational efficiency. The financial model of the company’s projects allows you to simulate cash flows of planned activities and assess the company’s future financial condition, shows where the company’s financial resources will come from and what they will be spent on, serves as the basis for risk analysis and the construction of the company’s risk management system, ensures continuous analytical work, significantly saves time, allowing to avoid consideration of unacceptable options and to quickly make a decision to terminate unpromising investment projects.